A positive electrode sheet, a method for manufacturing the same, a solid-state battery, and an electric device

CN122991996APending Publication Date: 2026-10-27ZHEJIANG INTELLIGENT TRANSPORTATION TECHNOLOGY INNOVATION CENTER +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611479195.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-22
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

现有物理共混、表面包覆等改性手段多为单一维度优化,难以同时兼顾离子通道连续性、界面结合稳定性与抗体积形变能力,使得正极片普遍存在着界面结合力弱、离子网络易失效等问题

Benefits of technology

[0019]本发明提供的正极片及其制备方法、固态电池、用电设备,通过在正极浆料中加入预聚物单体,在正极片制备过程中的干燥处理阶段原位聚合形成离子导电聚合物,能够使所制得的正极片具有低界面阻抗与优异界面稳定性,有助于提升固态电池的循环稳定性与倍率性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application provides a positive electrode sheet, a preparation method thereof, a solid-state battery and an electric device. The preparation method of the positive electrode sheet comprises the following steps: coating a positive electrode slurry comprising a prepolymer monomer and a positive electrode active material on at least one side surface of a positive electrode current collector, and after a drying treatment, forming a positive electrode active material layer containing an ion conductive polymer and the positive electrode active material, to obtain the positive electrode sheet; wherein the prepolymer monomer is polymerized to form the ion conductive polymer during the drying treatment. The prepared positive electrode sheet has low interface impedance and excellent interface stability, which helps to improve the cycle stability and rate performance of the solid-state battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of new energy batteries, and in particular to a positive electrode sheet and its preparation method, a solid-state battery, and electrical equipment. Background Technology

[0002] With the rapid development of the new energy storage and electric vehicle industries, high-energy-density and high-safety rechargeable batteries have become a core research and development direction in the industry. Solid-state batteries use non-flammable solid electrolytes to replace traditional liquid electrolytes, fundamentally solving the safety hazards of liquid batteries. They are also compatible with high-specific-capacity positive and negative electrode materials, making them the mainstream technology for next-generation energy storage batteries. Among them, lithium-rich manganese-based positive electrode materials have ultra-high theoretical specific capacity and low raw material costs, and are considered a highly promising high-energy-density positive electrode system. Combining them with sulfide solid electrolytes to construct solid-state batteries is expected to achieve both high energy density and high safety, becoming a current research hotspot in the field of solid-state batteries.

[0003] However, cathode materials (such as lithium-rich manganese-based cathode materials) face severe technical bottlenecks in solid-state battery systems. On the one hand, the contact between the cathode active particles and the solid electrolyte particles is a solid-solid point, lacking a continuous ion conduction path, resulting in a significant increase in ion impedance within the electrode and severely limiting rate performance. On the other hand, during cycling, cathode materials (such as lithium-rich manganese-based materials) are prone to lattice oxygen release, layered phase to spinel phase transformation, and microcrack propagation, further damaging the already fragile ion transport network, leading to interface delamination, ion channel interruption, and rapid capacity decay. Existing modification methods such as physical blending and surface coating are mostly single-dimensional optimizations, making it difficult to simultaneously ensure ion channel continuity, interfacial bonding stability, and resistance to volumetric deformation. This results in cathode sheets generally exhibiting problems such as weak interfacial bonding and easy failure of the ion network.

[0004] Therefore, how to simultaneously construct continuous ion transport channels in solid cathodes, strengthen interfacial bonding, and buffer cyclic volume deformation, thereby solving problems such as high solid-solid contact impedance and poor cycle stability, and improving the rate performance and cycle stability of batteries, is a technical problem that urgently needs to be solved in this field. Summary of the Invention

[0005] This invention provides a positive electrode sheet and its preparation method, a solid-state battery, and an electrical device. The positive electrode sheet provided by this invention has characteristics such as low interfacial impedance, excellent interfacial stability, and low cycle volume deformation, which helps to improve the rate performance and cycle stability of solid-state batteries and effectively overcomes the defects of existing technologies.

[0006] In one aspect, the present invention provides a method for preparing a positive electrode sheet, comprising the following steps: coating a positive electrode slurry comprising a prepolymer monomer and a positive electrode active material onto at least one side surface of a positive electrode current collector, and after drying, forming a positive electrode active material layer containing an ion-conducting polymer and the positive electrode active material, thereby obtaining the positive electrode sheet; wherein the prepolymer monomer polymerizes during the drying process to form the ion-conducting polymer.

[0007] According to one embodiment of the present invention, the prepolymer monomer is prepolymerized from monomer raw materials, the monomer raw materials including a main monomer and a crosslinking monomer containing epoxy groups; and / or, the weight average molecular weight of the prepolymer monomer is 10,000-200,000.

[0008] According to one embodiment of the present invention, the mass ratio of the main monomer to the crosslinking monomer is 1:1 to 12:1; and / or, the main monomer includes imidazole monomers and / or piperidine monomers; the piperidine monomer includes N-allyl-N-methylpiperidine hexafluorophosphate; the imidazole monomer includes 1-vinyl-3-butylimidazolium trifluoromethanesulfonylimide, 1-vinyl-3-ethylimidazolium bis(trifluoromethanesulfonyl)imide, 1-allyl-3-methylimidazolium hexafluorophosphate, 1-allyl-3-butylimidazolium hexafluorophosphate, 1-allyl-3-butylimidazolium tetrafluoroborate, 1-allyl-3-ethylimidazolium hexafluorophosphate, 1-allyl-3-ethylimidazolium tetrafluoroborate, 1-allyl-3-methylimidazolium tetrafluoroborate, and 1-allyl-3-methylimidazolium tetrafluoroborate. The crosslinking monomer comprises one or more of the following: acid salts, 1-allyl-3-vinylimidazolium tetrafluoroborate; and / or, the crosslinking monomer comprises epoxy monomers; the epoxy monomers comprise one or more of the following: allyl glycidyl ether, glycidyl methacrylate, 3,4-epoxy-1-butene, neopentyl glycol diglycidyl ether, trimethylolpropane triglycidyl ether, polyethylene glycol diglycidyl ether, and triglycidyl isocyanurate; and / or, the monomer raw material further comprises alkenyl ester monomers, the alkenyl ester monomers comprising one or more of the following: tripropylene glycol diacrylate, triethylene glycol diacrylate, ethylene glycol dimethacrylate, dipropylene glycol diacrylate, methyl methacrylate, hexafluorobutyl methacrylate, butyl acrylate, and dipropylene adipate.

[0009] According to one embodiment of the present invention, the prepolymer monomer is prepolymerized from the monomer raw material in the presence of a first initiator, the first initiator including peroxide initiators and / or azo initiators; and / or, the reaction temperature of the prepolymerization is 50°C to 80°C, and the reaction time is 9h to 24h.

[0010] According to one embodiment of the present invention, the positive electrode slurry further includes a second initiator for initiating the polymerization of the prepolymer monomer during the drying process.

[0011] According to one embodiment of the present invention, the second initiator comprises a lithium salt.

[0012] According to one embodiment of the present invention, the lithium salt includes one or more of bis(trifluoromethane)sulfonylimide lithium salt, lithium difluoroborate, lithium hexafluorophosphate, and lithium tetrafluoroborate; and / or, in the positive electrode active material layer, the mass fraction of the lithium salt is 0.65% to 2%.

[0013] According to one embodiment of the present invention, in the positive electrode active material layer, the mass fraction of the ion-conducting polymer is 0.75% to 5%; and / or, in the positive electrode active material layer, the mass fraction of the positive electrode active material is 60% to 90%; and / or, the positive electrode active material includes lithium-rich manganese-based positive electrode active material.

[0014] According to one embodiment of the present invention, the positive electrode slurry further includes a conductive agent and a solid electrolyte.

[0015] According to one embodiment of the present invention, the conductive agent comprises one or more of single-walled carbon nanotubes, multi-walled carbon nanotubes, carbon nanofibers, graphite, carbon particles, carbon black, carbon microspheres, activated carbon, and graphene; and / or, in the positive electrode active material layer, the mass fraction of the conductive agent is 0.5% to 5%; and / or, the solid electrolyte comprises a sulfide solid electrolyte, wherein the sulfide solid electrolyte comprises Li6PS5Cl, Li 10 GeP2S 12 Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 One or more of the following; and / or, in the positive electrode active material layer, the mass fraction of the solid electrolyte is 5% to 20%.

[0016] In another aspect, the present invention provides a positive electrode sheet prepared according to the aforementioned method for preparing a positive electrode sheet.

[0017] In another aspect, the present invention provides a solid-state battery comprising the aforementioned positive electrode.

[0018] In another aspect, the present invention provides an electrical device including the aforementioned solid-state battery.

[0019] The positive electrode sheet, its preparation method, solid-state battery, and electrical device provided by this invention, by adding prepolymer monomers to the positive electrode slurry and polymerizing them in situ during the drying process of the positive electrode sheet preparation to form an ion-conducting polymer, can enable the prepared positive electrode sheet to have low interfacial impedance and excellent interfacial stability, which helps to improve the cycle stability and rate performance of solid-state batteries. Detailed Implementation

[0020] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions in the embodiments of this invention will be clearly and completely described below in conjunction with the embodiments of this invention. The specific embodiments listed below are merely descriptions of the principles and features of this invention, and the examples given are only for explaining this invention and are not intended to limit the scope of this invention. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.

[0021] This invention provides a method for preparing a positive electrode sheet, comprising the following steps: coating a positive electrode slurry comprising a prepolymer monomer and a positive electrode active material onto at least one side surface of a positive electrode current collector, and after drying, forming a positive electrode active material layer containing an ion-conducting polymer and a positive electrode active material, thereby obtaining a positive electrode sheet; wherein, the prepolymer monomer polymerizes to form an ion-conducting polymer during the drying process.

[0022] In this embodiment of the invention, during the above preparation process, a prepolymer monomer is added to the positive electrode slurry. The prepolymer monomer in the positive electrode slurry polymerizes during the drying stage of the positive electrode sheet preparation process, thereby forming an ion-conducting polymer in situ during the positive electrode sheet preparation process. This helps to build a cross-linked network in the formed positive electrode active material layer, reduces the interfacial resistance between particles such as positive electrode active materials in the formed positive electrode active material layer, and improves the bonding strength between particles. As a result, the prepared positive electrode sheet has comprehensive performance with low ion transport impedance, good interfacial stability, and excellent cycle retention rate. It can effectively alleviate problems such as high solid-solid point contact impedance, easy interface peeling, and easy failure of ion network in solid systems.

[0023] In summary, the embodiments of the present invention introduce prepolymer monomers during the preparation of the positive electrode to form ionic polymers through in-situ crosslinking, thereby simultaneously achieving multiple functions such as continuous ion channel construction, interfacial chemical bonding enhancement, and volume deformation buffering, overcoming the problems of ion transport bottleneck and poor cycle stability of solid positive electrodes.

[0024] In the preparation process of the above-mentioned positive electrode sheet, a process route is adopted in which prepolymer monomers are introduced into the positive electrode slurry (i.e., polymer monomers are introduced during the homogenization stage) and crosslinking is carried out simultaneously during drying treatment (such as baking). No additional particle coating or pretreatment process is required, which helps to ensure compatibility with existing lithium battery coating and drying production lines and reduce process modification costs. The in-situ crosslinking method allows the polymer network to be formed simultaneously with the solvent evaporation, resulting in a more uniform distribution. This helps to improve the continuity of ion pathways and the uniformity of interfacial bonding, and solves problems such as poor solid-solid contact and interfacial stability.

[0025] In some embodiments, the weight-average molecular weight of the prepolymer monomers is 10,000-200,000, for example, a range consisting of 10,000, 40,000, 80,000, 120,000, 160,000, 200,000, or any combination thereof. The molecular weight of the prepolymer directly affects the slurry viscosity, dispersion uniformity, and mechanical properties of the cross-linked network. A prepolymer weight-average molecular weight of not less than 10,000 helps to form a three-dimensional network with a certain chain segment length and flexibility after cross-linking, absorbing volume stress during the charging and discharging process through network deformation and alleviating particle interface delamination problems. A prepolymer weight-average molecular weight of not more than 200,000 helps to ensure the solubility of the prepolymer in the solvent and the appropriate viscosity of the slurry, promoting uniform dispersion of the prepolymer among various types of particles and improving the distribution uniformity of the three-dimensional network. Controlling the molecular weight within the above range is beneficial for balancing network flexibility and processing dispersibility, simultaneously adapting to electrochemical performance and preparation process requirements.

[0026] In some embodiments, the mass fraction of the ion-conducting polymer in the above-mentioned positive electrode active material layer is 0.75% to 5%, for example, 0.75%, 0.8%, 1%, 2%, 3%, 4%, 5%, or any combination thereof. A mass fraction of not less than 0.75% of the ion-conducting polymer helps to form a continuous, interconnected three-dimensional ion-conducting network between particles, ensuring the integrity of the ion transport pathway and reducing interfacial impedance. A mass fraction of not more than 5% of the ion-conducting polymer helps to control the proportion of inactive components and maintain a high loading of active material and energy density in the positive electrode. Controlling the mass fraction of the ion-conducting polymer within the above range is beneficial for balancing ion conductivity and electrode energy density, adapting to the comprehensive performance requirements of solid-state positive electrodes.

[0027] It should be noted that the prepolymer monomers polymerize to form ion-conducting polymers during the drying process. The mass of the ion-conducting polymers in the positive electrode active material layer is basically equal to the mass of the prepolymer monomers added to the positive electrode slurry. That is, the amount of prepolymer monomers used is such that the mass percentage of the ion-conducting polymers formed in the positive electrode active material layer is 0.75% to 5%. In other words, the mass percentage of the prepolymer monomers in the positive electrode slurry is 0.75% to 5% of the total mass of the components other than the solvent, for example, 0.75%, 0.8%, 1%, 2%, 3%, 4%, 5%, or any combination thereof.

[0028] In some embodiments, the prepolymer monomer can be prepolymerized from monomer raw materials, including a host monomer and a crosslinking monomer containing epoxy groups. During the above preparation process, the prepolymer monomer in the cathode slurry polymerizes during the drying stage of the cathode sheet preparation process, thereby forming an ion-conducting polymer in situ during cathode sheet preparation. This facilitates the construction of a crosslinking network in the formed cathode active material layer. Simultaneously, the prepolymer monomer is prepared by prepolymerization of monomer raw materials including a host monomer and a crosslinking monomer containing epoxy groups. The host monomer provides lithium-ion conductive structural units, ensuring the intrinsic ion conductivity of the polymer. The crosslinking monomer introduces epoxy functional groups, providing reaction sites for subsequent in-situ crosslinking and particle interface anchoring. The prepolymer monomer carries epoxy groups, which undergo two types of ring-opening reactions during the drying process. On the one hand, the epoxy groups on the molecular chains formed by the polymerization of different prepolymer monomers open their rings to form ether bonds and crosslink with each other. Together with the free radical addition of residual double bonds, they construct a continuous three-dimensional ion-conducting polymer network, filling the gaps between particles such as positive electrode active materials in the positive electrode active material layer. This expands the originally discrete solid-solid point contact into a surface contact connected by an ion conduction network, increasing the effective ion transport area, reducing interfacial ion impedance, and alleviating the core problem of discontinuous ion pathways. On the other hand, the epoxy groups can undergo ring-opening addition with the hydroxyl groups on the surface of particles such as positive electrode active materials, anchoring the polymer network to the surface of various particles through covalent ether bonds. This replaces the weak bonding mode of traditional physical blending and improves the interfacial bonding strength. At the same time, the three-dimensional network formed by crosslinking has a certain degree of chain segment flexibility, which can absorb the stress generated by the volume change of the positive electrode during charging and discharging through network deformation. This alleviates the problems of interfacial peeling and ion channel breakage caused by particle expansion and contraction, and better maintains the integrity of the ion conduction network during cycling.

[0029] In some embodiments, the mass ratio of the main monomer to the crosslinking monomer is 1:1 to 12:1, for example, 1:1, 3:1, 5:1, 7:1, 9:1, 11:1, 12:1, or any combination thereof. A mass ratio of not less than 1:1 helps ensure the proportion of ion-conducting structural units in the polymer network, maintains high lithium-ion conduction efficiency, and reduces the internal ion impedance of the cathode. A mass ratio of not more than 12:1 helps provide sufficient crosslinking and anchoring points, ensuring the structural integrity of the three-dimensional network and the interfacial chemical bonding strength. Controlling the mass ratio within the above range is beneficial for balancing ion conduction performance and crosslinking interface performance, thereby optimizing the overall electrochemical performance.

[0030] In this invention, the master monomer is the main monomer that forms the prepolymer monomer as a prepolymer, that is, it is the main component in the monomer raw material. Specifically, the master monomer can be an unsaturated functional monomer that can undergo free radical polymerization reaction and is used to construct the main chain of the prepolymer monomer molecule.

[0031] In some embodiments, the host monomers include imidazole monomers and / or piperidine monomers. Imidazole and piperidine monomers can promote the dissociation of lithium salts, release migratory lithium ions, and assist lithium ion transport through polymer chain segment movement, thereby providing ion conduction capabilities for the three-dimensional network.

[0032] In some embodiments, piperidine monomers include N-allyl-N-methylpiperidine hexafluorophosphate; imidazole monomers include one or more of 1-vinyl-3-butylimidazolium trifluoromethanesulfonylimide, 1-vinyl-3-ethylimidazolium bis(trifluoromethanesulfonyl)imide, 1-allyl-3-methylimidazolium hexafluorophosphate, 1-allyl-3-butylimidazolium hexafluorophosphate, 1-allyl-3-butylimidazolium tetrafluoroborate, 1-allyl-3-ethylimidazolium hexafluorophosphate, 1-allyl-3-ethylimidazolium tetrafluoroborate, 1-allyl-3-methylimidazolium tetrafluoroborate, and 1-allyl-3-vinylimidazolium tetrafluoroborate. The selection of the above-mentioned piperidine and imidazole monomers as ion-conducting units helps to endow the cross-linked polymer with stable lithium-ion conductivity, construct a continuous ion transport pathway, and alleviate the problem of high ion impedance caused by solid-solid point contact. The two types of nitrogen-containing heterocyclic structures have good chemical and electrochemical stability, which helps to adapt to the high operating voltage of lithium-rich manganese groups and reduce side reactions in the cycling process.

[0033] In some embodiments, the crosslinking monomers include epoxy monomers; the epoxy monomers include one or more of allyl glycidyl ether, glycidyl methacrylate, 3,4-epoxy-1-butene, neopentyl glycol diglycidyl ether, trimethylolpropane triglycidyl ether, polyethylene glycol diglycidyl ether, and triglycidyl isocyanate. Epoxy monomers provide epoxy functional groups, which helps to achieve in-situ crosslinking and covalent anchoring on the particle surface, simultaneously solving the two major problems of ion channel continuity and interfacial bonding strength.

[0034] Specifically, in the preparation process of the aforementioned prepolymer monomers, the monomer raw materials may also include alkenyl ester monomers. Alkenyl ester monomers include one or more of the following: tripropylene glycol diacrylate, triethylene glycol diacrylate, ethylene glycol dimethacrylate, dipropylene glycol diacrylate, methyl methacrylate, hexafluorobutyl methacrylate, butyl acrylate, and diallyl adipate. Alkenyl ester monomers help extend the chain of the prepolymer monomers and adjust the crosslinking density and segment flexibility of the three-dimensional network, further enhancing the network's buffering capacity against volume deformation.

[0035] In some embodiments, the prepolymer monomer is prepolymerized from the aforementioned monomer raw materials in the presence of a first initiator, which includes peroxide initiators and / or azo initiators. Both azo and peroxide initiators can decompose to generate free radicals under heating conditions, triggering free radical addition polymerization of the carbon-carbon double bonds between the host monomer and the crosslinking monomer, stably obtaining functional prepolymers within the target molecular weight range. Both types of initiators are commonly used systems for free radical polymerization, with mature processes and good reproducibility, which is beneficial for the large-scale and stable synthesis of prepolymers.

[0036] Specifically, the aforementioned peroxide initiators include one or more of benzoyl peroxide, tert-butyl peroxide, diisopropyl peroxide, dicyclohexyl peroxide, and dilauryl peroxide.

[0037] Specifically, the aforementioned azo initiators include one or more of azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, azobisisovalerate, and azobiscyclohexylformitrile.

[0038] Specifically, the mass ratio of the monomer raw material to the first initiator can be 100:2 to 100:0.1, for example, 100:2, 100:1.6, 100:1.2, 100:0.8, 100:0.4, 100:0.1 or any combination thereof.

[0039] In some specific embodiments, when the monomer raw material is composed of a main monomer, a crosslinking monomer, and an alkenyl ester monomer, the mass ratio of the sum of the main monomer, the crosslinking monomer, and the alkenyl ester monomer to the mass ratio of the first initiator is 100:2 to 100:0.1, for example, 100:2, 100:1.6, 100:1.2, 100:0.8, 100:0.4, 100:0.1, or any combination thereof.

[0040] In some embodiments, the reaction temperature of the prepolymerization is 50°C to 80°C, for example, a range of 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, or any combination thereof. A prepolymerization reaction temperature not lower than 50°C helps ensure the effective decomposition rate of the first initiator and the smooth progress of the prepolymerization reaction, improving monomer conversion. A prepolymerization reaction temperature not higher than 80°C helps control the reaction rate steadily and avoids excessively wide molecular weight distribution affecting the subsequent slurry dispersibility. The prepolymerization time is 9h to 24h, for example, a range of 9h, 10h, 12h, 14h, 16h, 18h, 20h, 22h, 24h, or any combination thereof. A prepolymerization time not lower than 9h helps ensure sufficient monomer conversion and obtain a structurally stable prepolymer product. A prepolymerization time not higher than 24h helps balance synthesis efficiency and production economy. Controlling the temperature and time of the prepolymerization reaction within the above ranges is beneficial for obtaining prepolymer monomers with suitable molecular weight and uniform distribution.

[0041] Specifically, the aforementioned prepolymer monomer is prepared by the following method: In a protective atmosphere such as argon, monomer raw materials such as the main monomer and crosslinking monomer are mixed with a first initiator and a first organic solvent, and then a prepolymerization reaction is carried out. After the reaction is completed, the polymerization product is washed and dried (specifically, vacuum drying can be performed) to obtain the aforementioned prepolymer monomer. Specifically, conventional heating methods such as oil bath heating can be used to control the reaction temperature.

[0042] Specifically, the first organic solvent may include ethyl methyl carbonate.

[0043] Specifically, the above-mentioned prepolymerization reaction can be carried out under stirring, and the stirring speed can be 200 r / min to 800 r / min, for example, 200 r / min, 300 r / min, 400 r / min, 500 r / min, 600 r / min, 700 r / min, 800 r / min or any combination thereof.

[0044] Specifically, in this invention, a second organic solvent can be used to wash the polymerization product.

[0045] Specifically, the aforementioned second organic solvent may include one or more of alcohol solvents, ketone solvents, hydrocarbon solvents, and ester solvents; alcohol solvents include one or more of anhydrous ethanol, isopropanol, n-propanol, isobutanol, n-butanol, tert-butanol, and pentanol; ketone solvents include one or more of acetone, butanone, methyl isobutyl ketone, and methyl propyl ketone; hydrocarbon solvents include one or more of pentane, hexane, heptane, cyclohexane, and toluene; and ester solvents include one or more of ethyl acetate and isopropyl acetate.

[0046] Specifically, the vacuum drying temperature can be 60℃~80℃, for example, a range of 60℃, 65℃, 70℃, 75℃, 80℃ or any combination thereof; the vacuum drying pressure is ≤-0.09MPa. In this embodiment of the invention, conventional vacuum drying equipment and conventional vacuum drying methods can be used for vacuum drying, and there are no particular limitations on this.

[0047] In this embodiment of the invention, the positive electrode slurry also includes a second initiator for initiating the polymerization of prepolymer monomers during the drying process. The presence of the second initiator can initiate the polymerization reaction of the prepolymer monomers, thereby forming an ion-conducting polymer through in-situ polymerization during the preparation of the positive electrode sheet.

[0048] In some embodiments, the second initiator includes a lithium salt. The lithium salt, as the second initiator, has better compatibility with the prepolymer monomer formed by prepolymerization of monomer raw materials including the aforementioned main monomer and crosslinking monomers containing epoxy groups. It can initiate in-situ polymerization of the prepolymer monomer during the drying process in the preparation of the positive electrode sheet, thereby forming an ion-conducting polymer in-situ in the formed positive electrode active material layer. An ion-conducting polymer crosslinking network is constructed in-situ in the positive electrode active material layer, reducing the interfacial resistance between materials in the positive electrode active material layer and improving the bonding strength between material particles. At the same time, the lithium salt can also increase the concentration of migratable lithium ions in the positive electrode active material layer and improve the ion conduction performance of the positive electrode active material layer.

[0049] In some embodiments, the lithium salt includes one or more of bis(trifluoromethane)sulfonylimide lithium salt, lithium difluoroborate, lithium hexafluorophosphate, and lithium tetrafluoroborate. These types of lithium salts can better initiate the polymerization of prepolymer monomers during the drying stage of the cathode preparation process. Simultaneously, in the resulting cathode, the lithium ions generated by the dissociation of the lithium salt serve as the source of charge carriers for ion conduction. Introducing lithium salts into the cathode active material layer helps to increase the concentration of migratable lithium ions in the ion-conducting polymer network, further reducing ion transport impedance and improving rate performance. The availability of various fluorinated lithium salts allows for flexible adjustments based on the electrolyte system and voltage window, optimizing interfacial compatibility and ion conduction efficiency.

[0050] In some embodiments, the mass fraction of lithium salt in the above-mentioned positive electrode active material layer is 0.65% to 2%, for example, 0.65%, 0.7%, 1.0%, 1.3%, 1.6%, 1.9%, 2%, or any combination thereof. A lithium salt mass fraction of not less than 0.65% not only helps to initiate in-situ polymerization of prepolymer monomers during the drying process, but also helps to provide a more sufficient number of migratable lithium-ion carriers in the formed positive electrode active material layer, improving the ionic conductivity of the ion-conducting polymer network and reducing the internal ionic impedance of the positive electrode. A lithium salt mass fraction of not more than 2% helps to avoid excessive lithium salt agglomeration affecting ion transport efficiency, while maintaining the structural stability and flexibility of the polymer network. Controlling the lithium salt content within the above range is beneficial for optimizing the ion conduction performance of the polymer network and further improving the ion transport bottleneck at the solid-solid interface.

[0051] In the preparation process of the positive electrode sheet, the mass ratio of lithium salt in the positive electrode slurry to the total mass of other components in the positive electrode slurry, excluding the solvent, is basically equal to the mass fraction of lithium salt in the formed positive electrode active material layer. That is, the mass ratio of lithium salt in the positive electrode slurry to the total mass of other components in the positive electrode slurry, excluding the solvent, is 0.65% to 2%, for example, 0.65%, 0.7%, 1.0%, 1.3%, 1.6%, 1.9%, 2%, or any combination thereof.

[0052] In some embodiments, the positive electrode active material includes a lithium-rich manganese-based positive electrode active material.

[0053] Lithium-rich manganese-based cathode active materials possess advantages such as high specific capacity and high operating voltage, making them ideal materials for constructing high-energy-density solid-state batteries. However, these materials are prone to significant volume deformation during charge and discharge, easily damaging the fragile solid-solid interface of the solid-state system, causing ion conduction channel breakage, and leading to severe capacity decay. The cathode preparation method provided in this invention uses prepolymer monomers to form an ion-conducting polymer through dry in-situ polymerization, and introduces epoxy groups to construct a three-dimensional ion-conducting network that combines covalent anchoring and flexible buffering capabilities. This network can adapt to the volume change characteristics of lithium-rich manganese-based materials, continuously maintaining continuous ion transport pathways around the cathode active material particles. The combination of lithium-rich manganese-based cathode active materials and ion-conducting polymers fully leverages the high lithium storage capacity of lithium-rich manganese-based materials, significantly improving the energy density of solid-state batteries. Simultaneously, the ion-conducting polymer stabilizes the solid-solid interface, alleviating the long-standing problems of high interfacial impedance and rapid capacity decay in lithium-rich manganese-based cathodes in solid-state systems.

[0054] In some embodiments, the mass fraction of the positive electrode active material in the above-mentioned positive electrode active material layer is 60% to 90%, for example, 60%, 65%, 70%, 75%, 80%, 85%, 90%, or any combination thereof. A mass fraction of not less than 60% helps ensure that the positive electrode has a high specific capacity and energy density, leveraging the high capacity advantage of lithium-rich manganese-based materials; a mass fraction of not more than 90% helps reserve sufficient proportion for conductive agents, solid electrolytes, and ion-conducting polymers, constructing a complete electron and ion dual-continuous conduction network; controlling the proportion of active material within the above range is beneficial for balancing energy density and electrochemical performance.

[0055] In the preparation process of the positive electrode sheet, the mass ratio of the positive electrode active material in the positive electrode slurry to the total mass of the other components in the positive electrode slurry, excluding the solvent, is basically equal to the mass fraction of the positive electrode active material in the formed positive electrode active material layer. That is, the mass ratio of the positive electrode active material in the positive electrode slurry to the total mass of the other components in the positive electrode slurry, excluding the solvent, is 60% to 90%, for example, 60%, 65%, 70%, 75%, 80%, 85%, 90%, or any combination thereof.

[0056] In some embodiments, the positive electrode active material layer further includes a conductive agent and a solid electrolyte. The positive electrode active material serves as the lithium storage host, providing the electrode with basic capacity and energy density; the conductive agent constructs an efficient electron transport network, reduces electrode electronic impedance, and alleviates polarization problems; the solid electrolyte and the ion-conducting polymer form an organic-inorganic composite ion transport system, enriching the ion conduction pathways; the components are mutually compatible and synergistic, further optimizing the electrode's dual conduction network, stabilizing the interface structure, and improving the rate performance and cycle stability of the solid cathode.

[0057] The aforementioned conductive agents include one or more of single-walled carbon nanotubes, multi-walled carbon nanotubes, carbon nanofibers, graphite, carbon particles, carbon black, carbon microspheres, activated carbon, and graphene. Carbon-based conductive agents help construct continuous electronic conduction pathways within the cathode, compensating for the low fundamental electronic conductivity of lithium-rich manganese, ensuring rapid electron transport during electrochemical reactions, reducing cathode electronic impedance, and improving rate performance and the utilization rate of active materials.

[0058] In some embodiments, the mass fraction of the conductive agent in the above-mentioned positive electrode active material layer is 0.5% to 5%, for example, 0.5%, 1%, 2%, 3%, 4%, 5%, or any combination thereof. A mass fraction of conductive agent not less than 0.5% helps to form a continuous electronic conductive network inside the positive electrode, ensuring rapid electron transport and reducing electrode polarization; a mass fraction of conductive agent not more than 5% helps to control the proportion of inactive components, maintaining a high active material load and energy density; controlling the conductive agent content within the above range is beneficial for balancing electronic conductivity and electrode energy density, adapting to the comprehensive requirements of lithium-rich manganese-based solid-state positive electrodes.

[0059] In the preparation process of the positive electrode sheet, the mass ratio of the conductive agent in the positive electrode slurry to the total mass of the other components in the positive electrode slurry, excluding the solvent, is basically equal to the mass fraction of the conductive agent in the formed positive electrode active material layer. That is, the mass ratio of the conductive agent in the positive electrode slurry to the total mass of the other components in the positive electrode slurry, excluding the solvent, is 0.5% to 5%, for example, 0.5%, 1%, 2%, 3%, 4%, 5%, or any combination thereof.

[0060] In some embodiments, the solid electrolyte includes a sulfide solid electrolyte, which includes Li6PS5Cl, Li 10 GeP2S 12 Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 One or more of the following. Sulfide solid electrolytes have high room temperature ionic conductivity and are relatively soft, allowing for close contact with active particles upon cold pressing. They are key inorganic components for constructing ion conduction pathways within the cathode of solid-state batteries. Using sulfide solid electrolytes as the inorganic ion conduction component within the cathode helps provide basic ion transport capabilities and is suitable for the liquid-free system design of solid-state batteries. Combined with in-situ cross-linked ion-conducting polymer networks, they can further compensate for interfacial gaps at solid-solid point contacts, improving overall ion conduction efficiency.

[0061] In some embodiments, the mass fraction of the solid electrolyte in the above-mentioned positive electrode active material layer is 5% to 20%, for example, 5%, 8%, 12%, 15%, 18%, 20%, or any combination thereof. A solid electrolyte mass fraction of not less than 5% helps to provide sufficient inorganic ion conduction sites within the positive electrode, working in conjunction with the polymer network to construct ion transport pathways and reduce ion impedance. A solid electrolyte mass fraction of not more than 20% helps to ensure the main proportion of the active material, maintaining a high specific capacity and energy density of the positive electrode. Controlling the solid electrolyte content within the above range is beneficial for balancing ion conduction performance and energy density, achieving optimization of the overall performance of the solid positive electrode.

[0062] In the preparation process of the positive electrode sheet, the mass ratio of the solid electrolyte in the positive electrode slurry to the total mass of the components other than the solvent in the positive electrode slurry is basically equal to the mass fraction of the solid electrolyte in the formed positive electrode active material layer. That is, the mass ratio of the solid electrolyte in the positive electrode slurry to the total mass of the components other than the solvent in the positive electrode slurry is 5% to 20%, for example, 5%, 8%, 12%, 15%, 18%, 20% or any two of them.

[0063] Specifically, a positive electrode active material layer can be provided on one side of the positive electrode current collector, or positive electrode active material layers can be provided on both sides of the positive electrode current collector in the thickness direction.

[0064] Specifically, the above-mentioned positive electrode slurry includes a solvent (hereinafter referred to as the positive electrode solvent), and the positive electrode solvent may include N-methylpyrrolidone (NMP).

[0065] In practice, the prepolymer monomer and lithium salt are dissolved in the positive electrode solvent to obtain a mixed solution; a conductive agent, a solid electrolyte and a positive electrode active material are added to the mixed solution in sequence and stirred until they are basically completely dispersed to obtain a positive electrode slurry; the positive electrode slurry is coated on the surface of the positive electrode current collector to obtain a positive electrode slurry coating, and after drying, a positive electrode sheet is obtained.

[0066] Specifically, the solid content of the aforementioned positive electrode slurry is 65% to 70%, for example, a range consisting of 65%, 66%, 67%, 68%, 69%, 70%, or any two of these. The solid content of the aforementioned positive electrode slurry refers to the ratio of the total mass of all components other than the solvent to the total mass of the positive electrode slurry; that is, the solid content of the positive electrode slurry is substantially equal to the ratio of the total mass of all solid components forming the positive electrode active material layer to the total mass of the positive electrode slurry. For example, the solid components forming the positive electrode active material layer may consist of, for example, positive electrode active material, solid electrolyte, conductive agent, prepolymer monomer, and lithium salt.

[0067] Controlling the solid content of the cathode slurry within the range of 65% to 70%, with a solid content of no less than 65%, helps reduce the amount of organic solvent used in the slurry, shortens the solvent evaporation time during the electrode baking stage, improves production and processing efficiency, and reduces the probability of abnormal agglomeration of the polymer network during the drying process. A solid content of no more than 70% helps maintain suitable rheological properties of the slurry, ensures uniform dispersion of each solid phase particle and prepolymer monomer, avoids defects such as coating streaks and particle agglomeration caused by excessively high slurry viscosity, and facilitates the formation of a uniformly distributed three-dimensional ion conduction network inside the electrode.

[0068] Specifically, the positive current collector mentioned above includes aluminum foil.

[0069] Specifically, the thickness of the aforementioned positive electrode current collector is 5μm to 10μm, for example, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, or any combination thereof. A current collector thickness of not less than 5μm helps ensure the mechanical strength of the current collector itself, reduces the risk of foil breakage and wrinkling during coating and rolling processes, and provides a continuous and complete electronic conduction substrate, reducing the overall electronic impedance of the electrode. A current collector thickness of not more than 10μm helps reduce the proportion of inactive components in the current collector itself, reduces the overall ineffective weight of the electrode, and improves the energy density of the solid-state battery cell. Controlling the current collector thickness within the above range can balance the electrode processing stability and the battery energy density requirements.

[0070] Specifically, the thickness of the aforementioned cathode slurry coating can be 50μm to 100μm, for example, 50μm, 60μm, 70μm, 80μm, 90μm, 100μm, or any combination thereof. A coating thickness of not less than 50μm can support a sufficient amount of lithium-rich manganese-based cathode active material, ensuring that the electrode has sufficient lithium storage capacity and can leverage its high energy density advantage. A coating thickness of not more than 100μm can shorten the heat conduction distance during the baking stage, promote the uniform ring-opening crosslinking of the prepolymer epoxy groups, avoid the problems of incomplete crosslinking and uneven ion network distribution within the coating, and at the same time alleviate the stress accumulation during charging and discharging of thick coatings, reducing the phenomenon of interfacial delamination. Limiting the coating thickness to this range is beneficial for balancing electrode capacity, crosslinking uniformity, and cycle interface stability.

[0071] Specifically, in the preparation process of the above-mentioned positive electrode sheet, the drying temperature can be 85℃~100℃, for example, 85℃, 88℃, 92℃, 95℃, 98℃, 100℃ or any combination thereof; the drying time can be 12h~20h, for example, 12h, 14h, 16h, 18h, 20h or any combination thereof.

[0072] In this embodiment of the invention, the drying process can be carried out through conventional drying procedures in the preparation of the positive electrode sheet, such as baking, and the temperature of the drying process can be controlled by conventional methods, without any particular limitation.

[0073] Generally, after the drying process is completed, the electrode sheet can be rolled. The rolling process can be carried out using conventional process conditions in this field, and this invention does not impose any particular limitations on it.

[0074] This invention provides a positive electrode sheet, which is prepared by the above-described method for preparing a positive electrode sheet. Its advantages are as described above and will not be repeated here.

[0075] Specifically, the positive electrode sheet includes a positive electrode active material layer, which includes a positive electrode active material and an ion-conducting polymer. The positive electrode active material layer is formed by drying a positive electrode slurry, which includes a positive electrode active material and a prepolymer monomer. The prepolymer monomer is polymerized during the drying process to form an ion-conducting polymer. The prepolymer monomer is prepolymerized from a main monomer and a crosslinked monomer containing epoxy groups.

[0076] In addition, as mentioned above, the positive electrode active material layer may also include components such as lithium salt, conductive agent, and solid electrolyte. The optional types and amounts of each component are described above and will not be repeated here.

[0077] This invention also provides a solid-state battery, including the aforementioned positive electrode sheet.

[0078] The cathode sheet provided by this invention possesses excellent interface compatibility characteristics, making it perfectly compatible with sulfide-based solid-state battery systems. Lithium-rich manganese-based cathode active particles and Li6PS5Cl sulfide solid electrolyte particles can be interconnected via ion-conducting prepolymers to construct a continuous composite ion conduction network penetrating the interior of the cathode. The epoxy functional groups carried by the prepolymer molecular chains can undergo in-situ chemical reactions at the solid-solid interface of the active material and solid electrolyte during the electrode drying process, forming a dense and stable covalently bonded interface layer. This covalent bonding significantly strengthens the interfacial bonding force between heterogeneous particles, effectively buffering the volume deformation caused by lattice evolution during charging and discharging of the lithium-rich manganese-based cathode. It fundamentally suppresses interface degradation phenomena such as solid-solid interface loosening, interface peeling, and ion conduction pathway breakage during cycling, thus mitigating the problem of continuously increasing interface impedance on the cathode side during battery cycling.

[0079] Based on the aforementioned excellent interface compatibility and stability characteristics, the solid-state battery assembled using the positive electrode sheet provided by this invention can effectively reduce the ion transport impedance on the positive electrode side and improve the battery's rate charge and discharge performance. The stable solid-solid interface constructed by chemical bonding helps to alleviate the capacity decay problem during long-term cycling, effectively extending the battery's cycle life and long-term service stability. At the same time, it fully leverages the core advantage of the ultra-high specific capacity of lithium-rich manganese-based materials, improving the overall energy density of the solid-state battery and helping to achieve a breakthrough in comprehensive electrochemical performance with high energy, high rate, and long life.

[0080] Furthermore, this cathode system can be directly matched with Li6PS5Cl-based sulfide composite electrolyte membranes and adapted to lithium metal anodes to construct a complete solid-state battery system. Addressing the technical pain points of poor interfacial compatibility and frequent irreversible interfacial side reactions in the direct composite of sulfide electrolytes and lithium-rich manganese-based cathodes in existing technologies, this invention significantly suppresses the occurrence of interfacial side reactions by constructing an integrated interface modification structure in situ using prepolymers, while ensuring efficient and stable lithium-ion migration. Simultaneously, this invention eliminates the need for an additional interface modification coating process, simplifying the battery manufacturing process; and the cathode slurry system has a wide processing window, is highly compatible with existing electrode coating and roll forming mass production processes, exhibiting excellent process versatility and mass production capability, making it suitable for large-scale preparation of high-performance sulfide-based solid-state lithium-ion batteries.

[0081] Generally, a battery consists of a positive electrode and a negative electrode, as well as a solid electrolyte membrane located between the positive and negative electrodes.

[0082] Specifically, a solid-state battery includes a cell and a casing that encapsulates the cell. The cell includes a positive electrode, a solid electrolyte membrane, and a negative electrode. The solid electrolyte membrane is located between the positive and negative electrodes to separate them and prevent short circuits. At the same time, the solid electrolyte membrane also allows active ions such as lithium ions to pass through, so that active ions such as lithium ions can be inserted and extracted between the positive and negative electrodes, thus realizing the charging and discharging process of the battery.

[0083] In this embodiment of the invention, the battery cell can be packaged using conventional housing materials in the art, such as flexible packaging materials like aluminum-plastic film, but is not limited thereto.

[0084] In addition, the negative electrode sheet may include a metal negative electrode sheet, specifically a lithium metal negative electrode sheet (i.e., the negative electrode sheet is a lithium metal negative electrode), but is not limited thereto. In other embodiments, the negative electrode sheet may also include a negative current collector and a negative electrode coating located on at least one side surface of the negative current collector. Specifically, the negative electrode coating may be provided on one side surface of the negative current collector, or negative electrode coatings may be provided on both sides of the negative current collector in the thickness direction.

[0085] Specifically, the aforementioned negative electrode active material layer may include materials such as negative electrode active material, conductive agent, and binder. These materials can be conventional materials in the art. For example, the negative electrode active material may include one or more of silicon-based materials, siloxy-based materials, silicon-carbon-based materials, graphite, lithium metal, and lithium-indium alloy materials. Graphite may include artificial graphite and / or natural graphite. The conductive agent may include one or more of conductive carbon black, carbon nanotubes (CNT), acetylene black, graphene, Ketjen black, and carbon fiber. The binder may include one or more of sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamide-imide, polyvinyl alcohol, and sodium polyacrylate.

[0086] The embodiments of the present invention may employ conventional negative electrode current collectors in the art, for example, negative electrode current collectors include copper foil.

[0087] In this embodiment of the invention, the negative electrode sheet can be prepared by conventional methods in the art, such as by coating. Specifically, the components used to form the negative electrode active material, conductive agent, binder and other components can be dispersed in the negative electrode solvent, such as water (deionized water can be used), to prepare a negative electrode slurry, which is then coated on the surface of the negative electrode current collector. After drying, rolling and other processes, the negative electrode sheet is obtained.

[0088] In this embodiment of the invention, solid-state batteries can be prepared by conventional methods in the art. The preparation process may include: assembling a positive electrode, an electrolyte membrane, and a negative electrode layer into a cell, and then encapsulating it with a casing to obtain a solid-state battery. All the processes involved are conventional preparation processes for solid-state batteries and are not particularly limited thereto.

[0089] This invention also provides an electrical device including the solid-state battery described above.

[0090] According to the inventors' research, electrical devices equipped with the aforementioned solid-state batteries can achieve higher energy density and longer battery life. The high safety of the solid-state system and the cycle stability of the battery help improve the safety of the device and its long-term service performance, making it suitable for various application scenarios such as consumer electronics, electric vehicles, and energy storage systems.

[0091] The electrical equipment used in the embodiments of the present invention can be conventional electrical equipment in the art, such as power equipment (e.g., electric vehicles, electric cars), electronic equipment (e.g., mobile phones, tablets, laptops, digital cameras, etc.), wearable devices (e.g., watches, bracelets, VR glasses, etc.), energy storage power stations, etc., and there are no particular limitations on this.

[0092] The present invention will be further described below through specific embodiments.

[0093] The raw materials used in the following examples and comparative examples can all be obtained through conventional techniques in the art, such as commercial purchases; sulfide electrolyte (LPSC): HNE-SSE-FN03.

[0094] In the following embodiments, the mass of the ion-conducting polymer in the positive electrode active material layer is basically equal to the mass of the prepolymer monomer added to the positive electrode slurry. The mass fraction of the ion-conducting polymer in the positive electrode active material layer = the mass of the prepolymer monomer / (mass of prepolymer monomer + mass of lithium salt + mass of conductive agent + mass of solid electrolyte + mass of positive electrode active material).

[0095] Example 1

[0096] S1. Preparation of prepolymer monomers

[0097] In an argon-filled glove box, 1.84 g of 1-allyl-3-ethylimidazolium tetrafluoroborate, 1.16 g of glycidyl methacrylate, and 3.6 mg of azobisisobutyronitrile were weighed and dissolved in 7 g of methyl ethyl carbonate. The solution was then vacuum-sealed and reacted in an oil bath at 65°C with stirring at 500 r / min for 24 h. After washing and precipitating, the precipitate was dried under vacuum at 60°C to obtain the prepolymer monomer. The weight-average molecular weight of the prepolymer monomer was 150,000.

[0098] S2, Preparation of the positive electrode

[0099] 0.86g of prepolymer monomer and 714mg of lithium hexafluorophosphate (lithium salt) were dissolved in 43g of NMP solvent and stirred until the prepolymer monomer was completely dissolved to obtain a mixed solution. 2g of single-walled carbon nanotubes (conductive agent) were added to the mixed solution and stirred until completely dispersed. Then, 10g of sulfide solid electrolyte Li6PS5Cl (HNE-SSE-FNO3) was added and stirred until completely dispersed. Finally, 85g of lithium-rich manganese-based positive electrode active material (Zhenhua New Materials ZH69RC1-P2) was added and stirred until completely dispersed to obtain a positive electrode slurry. The positive electrode slurry was coated on the surface of aluminum foil (8μm thick) to obtain a positive electrode slurry coating (80μm thick). After baking at 85℃ for 20h in a vacuum oven and a rolling process, a positive electrode sheet was obtained.

[0100] S3. Preparation of the mold battery: A Li6PS5Cl / SBR composite electrolyte membrane (Li6PS5Cl to SBR mass ratio of 98.5:1.5) is selected as the solid electrolyte membrane of the solid battery, and lithium metal foil is used as the negative electrode of the battery. The positive electrode sheet obtained in step S2 is used as the working positive electrode. The battery assembly is completed to obtain the mold battery for electrochemical performance testing.

[0101] Example 2

[0102] S1. Preparation of prepolymer monomers

[0103] In an argon-filled glove box, 2.2 g of 1-allyl-3-ethylimidazolium tetrafluoroborate, 0.17 g of 3,4-epoxy-1-butene, 0.63 g of triethylene glycol diacrylate, and 3.6 mg of azobisisobutyronitrile were weighed and dissolved in 7 g of methyl ethyl carbonate. The solution was then vacuum-sealed and reacted in an oil bath at 65°C with stirring at 500 r / min for 24 h. After washing and precipitating, the precipitate was dried under vacuum at 60°C to obtain the prepolymer monomer. The weight-average molecular weight of the prepolymer monomer was 145,000.

[0104] The remaining preparation steps and conditions are the same as in Example 1.

[0105] Example 3

[0106] S1. Preparation of prepolymer monomers

[0107] In an argon-filled glove box, 2.73 g of N-allyl-N-methylpiperidine hexafluorophosphate, 0.27 g of allyl glycidyl ether, and 3.6 mg of benzoyl peroxide were weighed and dissolved in 7 g of methyl ethyl carbonate. The solution was then vacuum-sealed and reacted in an oil bath at 60 °C with stirring at 500 r / min for 12 h. After washing and precipitating, the precipitate was dried under vacuum at 60 °C to obtain the prepolymer monomer. The weight-average molecular weight of the prepolymer monomer was 130,000.

[0108] The remaining preparation steps and conditions are the same as in Example 1.

[0109] Example 4

[0110] S1. Preparation of prepolymer monomers

[0111] In an argon-filled glove box, 2.74 g of 1-allyl-3-butylimidazolium tetrafluoroborate, 0.26 g of glycidyl methacrylate, and 3.6 mg of benzoyl peroxide were weighed and dissolved in 7 g of methyl ethyl carbonate. The solution was then vacuum-sealed and reacted in an oil bath at 80 °C with stirring at 500 r / min for 20 h. After washing and precipitating, the precipitate was dried under vacuum at 60 °C to obtain the prepolymer monomer. The weight average molecular weight of the prepolymer monomer was 10,000.

[0112] The remaining preparation steps and conditions are the same as in Example 1.

[0113] Example 5

[0114] S1. Preparation of prepolymer monomers

[0115] In an argon-filled glove box, 2.62 g of 1-allyl-3-methylimidazolium tetrafluoroborate, 0.23 g of glycidyl methacrylate, 0.15 g of methyl methacrylate, and 3.6 mg of benzoyl peroxide were weighed and dissolved in 7 g of methyl ethyl carbonate. The solution was then vacuum-sealed and reacted in an oil bath at 55°C with stirring at 500 r / min for 10 h. After washing and precipitating, the precipitate was dried under vacuum at 60°C to obtain the prepolymer monomer. The weight average molecular weight of the prepolymer monomer was 200,000.

[0116] The remaining preparation steps and conditions are the same as in Example 1.

[0117] Example 6

[0118] S1. Preparation of prepolymer monomers

[0119] In an argon-filled glove box, 2.88 g of 1-allyl-3-methylimidazolium tetrafluoroborate, 0.12 g of 3,4-epoxy-1-butene, and 6 mg of benzoyl peroxide were weighed and dissolved in 7 g of methyl ethyl carbonate. The solution was then vacuum-sealed and reacted in an oil bath at 60 °C with stirring at 500 r / min for 12 h. After washing and precipitating, the precipitate was dried under vacuum at 60 °C to obtain the prepolymer monomer. The weight-average molecular weight of the prepolymer monomer was 9000.

[0120] The remaining preparation steps and conditions are the same as in Example 1.

[0121] Example 7

[0122] S1. Preparation of prepolymer monomers

[0123] In an argon-filled glove box, 2.59 g of 1-allyl-3-methylimidazolium tetrafluoroborate, 0.15 g of glycidyl methacrylate, 0.29 g of tripropylene glycol diacrylate, and 3.6 mg of benzoyl peroxide were weighed and dissolved in 6.28 g of methyl ethyl carbonate. The solution was then vacuum-sealed and reacted in an oil bath at 85 °C and 500 r / min for 26 h. After washing and precipitating, the precipitate was dried under vacuum at 60 °C to obtain the prepolymer monomer. The weight-average molecular weight of the prepolymer monomer was 210,000.

[0124] The remaining preparation steps and conditions are the same as in Example 1.

[0125] Example 8

[0126] S2, Preparation of the positive electrode

[0127] 0.788g of prepolymer monomer and 714mg of lithium hexafluorophosphate were dissolved in 43g of NMP solvent and stirred until the prepolymer monomer was completely dissolved to obtain a mixed solution. 2g of single-walled carbon nanotubes were added to the mixed solution and stirred until completely dispersed. Then, 10g of sulfide solid electrolyte Li6PS5Cl (HNE-SSE-FNO3) was added and stirred until completely dispersed. Finally, 85g of lithium-rich manganese-based positive electrode active material (Zhenhua New Materials ZH69RC1-P2) was added and stirred until completely dispersed to obtain a positive electrode slurry. The positive electrode slurry was coated on the surface of aluminum foil (8μm thick) to obtain a positive electrode slurry coating (80μm thick). After baking at 85℃ for 20h in a vacuum oven and a rolling process, a positive electrode sheet was obtained.

[0128] The remaining preparation steps and conditions are the same as in Example 1.

[0129] Example 9

[0130] S2, Preparation of the positive electrode

[0131] 5.14 g of prepolymer monomer and 714 mg of lithium hexafluorophosphate were dissolved in 43 g of NMP solvent and stirred until the prepolymer monomer was completely dissolved to obtain a mixed solution. 2 g of single-walled carbon nanotubes were added to the mixed solution and stirred until completely dispersed. Then, 10 g of sulfide solid electrolyte Li6PS5Cl (HNE-SSE-FNO3) was added and stirred until completely dispersed. Finally, 85 g of lithium-rich manganese-based positive electrode active material (Zhenhua New Materials ZH69RC1-P2) was added and stirred until completely dispersed to obtain a positive electrode slurry. The positive electrode slurry was coated on the surface of aluminum foil (8 μm thick) to obtain a positive electrode slurry coating (80 μm thick). After baking at 85°C for 20 h in a vacuum oven and a rolling process, a positive electrode sheet was obtained.

[0132] The remaining preparation steps and conditions are the same as in Example 1.

[0133] Example 10

[0134] S2, Preparation of the positive electrode

[0135] 5.242g of prepolymer monomer and 714mg of lithium hexafluorophosphate were dissolved in 43g of NMP solvent and stirred until the prepolymer monomer was completely dissolved to obtain a mixed solution. 2g of single-walled carbon nanotubes were added to the mixed solution and stirred until completely dispersed. Then, 10g of sulfide solid electrolyte Li6PS5Cl (HNE-SSE-FNO3) was added and stirred until completely dispersed. Finally, 85g of lithium-rich manganese-based positive electrode active material (Zhenhua New Materials ZH69RC1-P2) was added and stirred until completely dispersed to obtain a positive electrode slurry. The positive electrode slurry was coated on the surface of aluminum foil (8μm thick) to obtain a positive electrode slurry coating (80μm thick). After baking at 85℃ for 20h in a vacuum oven and a rolling process, a positive electrode sheet was obtained.

[0136] The remaining preparation steps and conditions are the same as in Example 1.

[0137] Example 11

[0138] S2, Preparation of the positive electrode

[0139] 0.7486g of prepolymer monomer and 714mg of lithium bis(trifluoromethane)sulfonylimide were dissolved in 43g of NMP solvent and stirred until the prepolymer monomer was completely dissolved to obtain a mixed solution. 2g of carbon black was added to the mixed solution and stirred until completely dispersed. Then, 10g of sulfide solid electrolyte Li6PS5Cl (HNE-SSE-FNO3) was added and stirred until completely dispersed. Finally, 85g of lithium-rich manganese-based positive electrode active material (Zhenhua New Materials ZH69RC1-P2) was added and stirred until completely dispersed to obtain a positive electrode slurry. The positive electrode slurry was coated on the surface of aluminum foil (8μm thick) to obtain a positive electrode slurry coating (80μm thick). After baking at 85℃ for 20h in a vacuum oven and a rolling process, a positive electrode sheet was obtained.

[0140] The remaining preparation steps and conditions are the same as in Example 1.

[0141] Example 12

[0142] S1. Preparation of prepolymer monomers

[0143] In an argon-filled glove box, 1.84 g of 1-allyl-3-ethylimidazolium tetrafluoroborate (main monomer) and 3.6 mg of azobisisobutyronitrile (first initiator) were weighed and dissolved in 6.4 g of methyl ethyl carbonate. The solution was then vacuum-sealed and reacted in an oil bath at 65 °C with stirring at 500 r / min for 24 h. After washing and precipitating, the precipitate was dried under vacuum at 60 °C to obtain the prepolymer monomer. The weight average molecular weight of the prepolymer monomer was 60,000.

[0144] The remaining preparation steps and conditions are the same as in Example 1.

[0145] Comparative Example 1

[0146] S1, Preparation of the positive electrode

[0147] 0.86g of polyvinylidene fluoride (PVDF) was dissolved in 43g of NMP solvent to obtain a mixed solution. 2g of single-walled carbon nanotubes were added to the mixed solution and stirred until completely dispersed. Then, 10g of sulfide solid electrolyte Li6PS5Cl (HNE-SSE-FNO3) was added and stirred until completely dispersed. Finally, 85g of lithium-rich manganese-based positive electrode active material (Zhenhua New Materials ZH69RC1-P2) was added and stirred until completely dispersed to obtain a positive electrode slurry. The positive electrode slurry was coated on the surface of aluminum foil (8μm thick) to obtain a positive electrode slurry coating (80μm thick). After baking at 85℃ for 20h in a vacuum oven and undergoing a rolling process, a positive electrode sheet was obtained.

[0148] The remaining preparation steps and conditions are the same as in Example 1.

[0149] The weight-average molecular weight of the prepolymer monomers in each example and the battery performance in each example and comparative example were tested through the following procedures:

[0150] (1) Determination of the weight-average molecular weight of the prepolymer monomers: Tetrahydrofuran was used as the mobile phase, a polystyrene gel chromatography column was selected, the column temperature was set to 35℃, the mobile phase flow rate was 1.0 mL / min, and a differential refractive index detector was used for detection. A standard curve was plotted using narrow distribution polystyrene as a standard. The prepolymer monomer sample to be tested was prepared as a tetrahydrofuran solution of a certain concentration, filtered through a microporous membrane, and then injected for testing. The weight-average molecular weight of the sample was calculated based on the chromatographic elution curve and the standard curve.

[0151] (2) Methods for determining the discharge specific capacity and cycle performance of the battery: After standing at a constant temperature of 25℃ for 12 hours, electrochemical charge-discharge tests were performed. The test voltage range was matched to the working window of the lithium-rich manganese-based cathode. The specific test steps for each performance index are as follows:

[0152] 0.1C First Discharge Specific Capacity Test: The battery is charged at a constant current of 0.1C to the charging cutoff voltage. After standing for 10 minutes, it is discharged at a constant current of 0.1C to the discharge cutoff voltage. The discharge capacity corresponding to each gram of lithium-rich manganese-based positive electrode active material during this discharge process is recorded. This is the 0.1C first discharge specific capacity, in mAh / g.

[0153] 1C discharge specific capacity test: After completing the low-rate activation test, let the battery stand for 10 minutes; charge it with a constant current of 1C to the charging cutoff voltage, let it stand for 10 minutes, and then discharge it with a constant current of 1C to the discharge cutoff voltage. Record the discharge capacity corresponding to each gram of lithium-rich manganese-based positive electrode active material during this discharge process, which is the 1C discharge specific capacity, in mAh / g.

[0154] 100-cycle capacity retention test: First, an activation charge-discharge test was performed with a constant current of 0.1C, and the discharge specific capacity of the first 0.1C cycle was recorded. Then, a continuous constant current charge-discharge cycle test was performed with a constant current of 0.2C. Each cycle was performed according to the procedure of constant current charging to the charging cutoff voltage, resting for 10 minutes, and constant current discharging to the discharge cutoff voltage. This was repeated for 100 cycles, and the discharge specific capacity of the 100th cycle was recorded. The capacity retention rate after 100 cycles = (discharge specific capacity of the 100th cycle / discharge specific capacity of the first 0.1C cycle) × 100%.

[0155] Table 1

[0156]

[0157] Compared to Comparative Example 1, Examples 1 to 12, by adding prepolymer monomers to the cathode slurry and forming cross-linked ion-conducting polymers through in-situ polymerization during cathode drying, can simultaneously improve the rate performance and cycle performance of the battery. The reason for this is that Examples 1 to 12 form ion-conducting polymers in the cathode active material layer through in-situ polymerization, which can construct a continuous, flexible, covalently anchored three-dimensional ion conduction network in the cathode active material layer. This can effectively reduce the ion transport impedance on the cathode side and improve the rate performance, while also buffering the volume deformation of the lithium-rich manganese-based cathode and stabilizing the solid-solid interface. This significantly suppresses interface degradation and capacity decay during cycling, achieving synergistic optimization of high capacity, high rate, and long cycle life.

[0158] Table 1 also shows that when the prepolymer monomer is copolymerized from a main monomer and a crosslinked monomer containing epoxy groups, it helps to more significantly improve the rate performance and cycle performance of the battery. For example, compared with Example 12, the prepolymer monomers used in Examples 1 to 10 introduced crosslinked monomers containing epoxy groups during the preparation process, and the batteries exhibited higher rate performance and cycle performance.

[0159] Table 1 also shows that when the molecular weight of the prepolymer monomer is in the range of 10,000 to 200,000, it helps to further improve the rate performance and cycle performance of the battery. For example, compared with Examples 6 and 7, Examples 1 to 5, with the weight-average molecular weight of the prepolymer monomer in the range of 10,000 to 200,000, are more conducive to balancing the uniformity of prepolymer slurry dispersion and the flexibility of cross-linked networks, thereby further improving the rate performance and cycle stability of the battery.

[0160] Table 1 also shows that when the mass fraction of the ion-conducting polymer in the positive electrode active material layer is in the range of 0.75% to 5%, it helps to further balance the high-rate performance and cycle performance of the battery. For example, compared with Example 10, Examples 1, 8, and 9, with the mass fraction of the ion-conducting polymer in the positive electrode active material layer in the range of 0.75% to 5%, show higher cycle performance while maintaining high rate performance. The reason for this is that a mass fraction of the ion-conducting polymer in the positive electrode active material layer in the range of 0.75% to 5% is more conducive to building a continuous ion network in the positive electrode active material layer, resulting in good cycle stability of the positive electrode sheet, while also improving the three-dimensional cross-linked network structure and enhancing the interfacial anchoring effect between particles.

[0161] Table 1 also shows that using single-walled carbon nanotubes as a conductive agent and lithium hexafluorophosphate as a second initiator to initiate the polymerization of prepolymer monomers helps to further improve the rate performance and cycle performance of the battery. For example, compared with Example 11, Examples 1 to 10 use single-walled carbon nanotubes as a conductive agent and lithium hexafluorophosphate as a lithium salt, resulting in batteries with higher rate performance and cycle performance. The reason for this is that using single-walled carbon nanotubes as a conductive agent and lithium hexafluorophosphate as a second initiator, while also acting as a lithium salt, allows for better compatibility with the epoxy crosslinked ion-conducting polymer system (i.e., ion-conducting polymers formed by in-situ polymerization of prepolymer monomers). This synergistically constructs a more complete electron-ion dual conduction network, significantly reducing problems such as electrode polarization and interfacial impedance, and improving the electrode's ion transport efficiency and structural stability.

[0162] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a positive electrode sheet, characterized in that, Includes the following steps: A positive electrode slurry comprising a prepolymer monomer and a positive electrode active material is coated onto at least one side of a positive electrode current collector. After drying, a positive electrode active material layer containing an ion-conducting polymer and the positive electrode active material is formed, thereby obtaining the positive electrode sheet. The prepolymer monomers are polymerized during the drying process to form the ion-conducting polymer. The prepolymer monomer is prepolymerized from monomer raw materials, which include a main monomer and a crosslinking monomer containing epoxy groups. The main monomer includes imidazole monomers and / or piperidine monomers. The mass ratio of the main monomer to the crosslinking monomer is 1:1 to 12:

1.

2. The method for preparing the positive electrode sheet according to claim 1, characterized in that, The weight-average molecular weight of the prepolymer monomer is 10,000-200,000.

3. The method for preparing the positive electrode sheet according to claim 2, characterized in that, The piperidine monomers include N-allyl-N-methylpiperidine hexafluorophosphate; the imidazole monomers include one or more of the following: 1-vinyl-3-butylimidazolium trifluoromethanesulfonylimide, 1-vinyl-3-ethylimidazolium bis(trifluoromethanesulfonyl)imide, 1-allyl-3-methylimidazolium hexafluorophosphate, 1-allyl-3-butylimidazolium hexafluorophosphate, 1-allyl-3-butylimidazolium tetrafluoroborate, 1-allyl-3-ethylimidazolium hexafluorophosphate, 1-allyl-3-ethylimidazolium tetrafluoroborate, 1-allyl-3-methylimidazolium tetrafluoroborate, and 1-allyl-3-vinylimidazolium tetrafluoroborate. And / or, the crosslinking monomer includes epoxy monomers; the epoxy monomer includes one or more of allyl glycidyl ether, glycidyl methacrylate, 3,4-epoxy-1-butene, neopentyl glycol diglycidyl ether, trimethylolpropane triglycidyl ether, polyethylene glycol diglycidyl ether, and triglycidyl isocyanurate. And / or, the monomer raw material further includes alkenyl ester monomers, which include one or more of tripropylene glycol diacrylate, triethylene glycol diacrylate, ethylene glycol dimethacrylate, dipropylene glycol diacrylate, methyl methacrylate, hexafluorobutyl methacrylate, butyl acrylate, and dipropylene adipate.

4. The method for preparing the positive electrode sheet according to claim 2 or 3, characterized in that, And / or, the prepolymer monomer is prepolymerized from the monomer raw material in the presence of a first initiator, the first initiator including peroxide initiators and / or azo initiators; And / or, the reaction temperature of the prepolymer is 50℃~80℃, and the reaction time is 9h~24h.

5. The method for preparing the positive electrode sheet according to claim 1, characterized in that, The positive electrode slurry also includes a second initiator for initiating the polymerization of the prepolymer monomers during the drying process.

6. The method for preparing the positive electrode sheet according to claim 5, characterized in that, The second initiator includes a lithium salt.

7. The method for preparing the positive electrode sheet according to claim 6, characterized in that, The lithium salt includes one or more of bis(trifluoromethane)sulfonylimide lithium salt, lithium difluoroborate, lithium hexafluorophosphate, and lithium tetrafluoroborate; And / or, in the positive electrode active material layer, the mass fraction of the lithium salt is 0.65%~2%.

8. The method for preparing the positive electrode sheet according to claim 1 or 5, characterized in that, In the positive electrode active material layer, the mass fraction of the ion-conducting polymer is 0.75%~5%; And / or, in the positive electrode active material layer, the mass fraction of the positive electrode active material is 60%~90%; And / or, the positive electrode active material includes lithium-rich manganese-based positive electrode active material.

9. The method for preparing the positive electrode sheet according to claim 1 or 5, characterized in that, The positive electrode slurry also includes a conductive agent and a solid electrolyte.

10. The method for preparing the positive electrode sheet according to claim 9, characterized in that, The conductive agent includes one or more of the following: single-walled carbon nanotubes, multi-walled carbon nanotubes, carbon nanofibers, graphite, carbon particles, carbon black, carbon microspheres, activated carbon, and graphene. And / or, in the positive electrode active material layer, the mass fraction of the conductive agent is 0.5%~5%; And / or, the solid electrolyte includes a sulfide solid electrolyte, wherein the sulfide solid electrolyte includes Li6PS5Cl, Li 10 GeP2S 12 Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 One or more of the following; And / or, in the positive electrode active material layer, the mass fraction of the solid electrolyte is 5%~20%.

11. A positive electrode plate, characterized in that, The positive electrode is prepared according to the method described in any one of claims 1-10.

12. A solid-state battery, characterized in that, Includes the positive electrode sheet as described in claim 11.

13. An electrical appliance, characterized in that, Includes the solid-state battery as described in claim 12.